2017
DOI: 10.4049/jimmunol.1601935
|View full text |Cite
|
Sign up to set email alerts
|

Id2 Collaborates with Id3 To Suppress Invariant NKT and Innate-like Tumors

Abstract: Inhibitor of DNA binding (ID) proteins, including ID1-4, are transcriptional regulators involved in promoting cell proliferation and survival in various cell types. Although upregulation of Id proteins has been associated with a broad spectrum of tumors, recent studies have identified that ID3 plays a tumor suppressor role in the development of Burkitt’s lymphoma in humans and Hepatosplenic T cell lymphomas in mice. Here, we report rapid lymphoma development in Id2/Id3 double knockout (L-DKO) mice caused by un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Id3 has been reported to induce caspase3‐ and 9‐dependent apoptosis in human keratinocytes, and TRIB3 has been also reported to have an antiapoptotic role in gastric cancer cells exposed to anticancer drugs . Decreased Id3 and Atoh8 , and increased Trib3 were reported to be involved in tumor progression . Moreover, the analysis of human HCC data from TCGA disclosed that the increased expression of CD74 and TRIB3 and decreased expression of ATOH8 were also observed in human HCC, and the expression changes were related to poor prognosis (Figure ).…”
Section: Discussionmentioning
confidence: 98%
“…Id3 has been reported to induce caspase3‐ and 9‐dependent apoptosis in human keratinocytes, and TRIB3 has been also reported to have an antiapoptotic role in gastric cancer cells exposed to anticancer drugs . Decreased Id3 and Atoh8 , and increased Trib3 were reported to be involved in tumor progression . Moreover, the analysis of human HCC data from TCGA disclosed that the increased expression of CD74 and TRIB3 and decreased expression of ATOH8 were also observed in human HCC, and the expression changes were related to poor prognosis (Figure ).…”
Section: Discussionmentioning
confidence: 98%
“…It is likely that the depletion of Id proteins unleashes the “early,” pre-TCR-independent developmental program for iNKT and other innate-like T cells, which otherwise occurs at much lower frequencies on a wild-type genetic background. Consequently, we have also observed heterogeneous innate-like αβ T cell lymphomas derived from iNKT, CD1dTet − , or T FH cells in Id2/Id3-deficient mice ( 14 , 39 ). Cumulatively, our findings support a layered ( 21 ), rather than a parallel developmental structure that coordinates the distinct fates of iNKT and conventional αβT cells during T cell development in the thymus.…”
Section: Discussionmentioning
confidence: 72%
“…The loss of iNKT cells in L-DKO CD1d −/− mice emphasizes the critical role of the selection step in iNKT cell development ( 39 ). However, TCRα repertoire sequencing of preselection DP cells from these mice demonstrated an increased frequency of Vα14-Jα18 rearrangements, suggesting that the lack of Id proteins can promote iNKT-specific rearrangements prior to, and independent of their selection.…”
Section: Discussionmentioning
confidence: 99%
“…Id2 and/or Id3 also play tumor suppressor roles to prevent lymphomagenesis of gd, iNKT and innate-like T cells. In these studies, tumorigenesis can be attributed to direct dysregulation of cell cycle, NF-κB, cytokine-cytokine receptor interaction and innate-like developmental genes by high E2A activity [108][109][110]. Interestingly, although most lymphomas found in Id3-deficient mice are gdTCR + , some morphologically identical tumors express typical B cell markers, B220 and CD19 in the absence T cell-related markers [108].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in Myc expression was observed among some samples [108]. We have recently found that Id2 and Id3 also play tumor suppressor roles in invariant natural killer T (iNKT-) and innate-like tumors in mice [109]. These lymphomas develop much more rapidly than the gdT cell lymphomas in Id3-deficient mice, and display signs of chromosomal instability.…”
Section: Paradoxical Role Of Id Proteins In T Cell Lymphomasmentioning
confidence: 99%